ANALYSIS OF E-PROMOTION, PRODUCT QUALITY, AND PRODUCT INNOVATION ON SOMETHINC PRODUCT PURCHASE DECISIONS (CASE STUDY OF SOMETHINCOFFICIAL CONSUMERS OR INSTAGRAM FOLLOWERS) - Rizqi Qurrota A’yun Burhanuddin; Muhammad Yani; Tofan Tri Nugroho (Antis Publisher, 2024)
Background: The increasing role of e-promotion, product quality, and innovation in influencing consumer purchasing decisions has become paramount in the digital marketplace, particularly for brands like Somethinc targeting younger generations on social media platforms. Specific Background: Despite the growing relevance of Instagram as a promotional tool, there is a limited understanding of how these factors specifically impact purchasing decisions among Somethinc’s Instagram followers. Knowledge Gap: Previous studies have inadequately explored the interplay between e-promotion, product quality, and product innovation in the context of consumer behavior on social media, particularly for beauty products among Generation Z and Millennials. Aims: This research aims to examine the effects of e-promotion, product quality, and product innovation on purchasing decisions for Somethinc products, using a sample of 103 followers of the @somethincofficial Instagram account. Results: Utilizing a quantitative approach and the Partial Least Square (PLS) method for data analysis, the findings reveal that e-promotion, product quality, and product innovation all have significant positive effects on purchasing decisions. Novelty: The study contributes new insights into the specific impact of digital marketing strategies on consumer behavior within the beauty industry, particularly among younger demographics. Implications: The results suggest that Somethinc should enhance its electronic promotion efforts, maintain high product quality, and focus on continuous product innovation to foster consumer satisfaction and drive purchasing decisions. The research also highlights the need for further investigation into additional platforms like TikTok and Shopee to broaden understanding of consumer behavior across various social media channels.